Sustaining effective communication and job performance while working from home (WFH) among employees in organisation / Nurul Hani Halim and Ahlam Abdul Aziz - Halim, Nurul Hani; Abdul Aziz, Ahlam (Faculty of Communication and Media Studies (FCMS), 2023)
The Covid-19 pandemic has caused changes in the work arrangements of organizations. Nowadays, most organizations have shifted their work environment to working from home. Thus, the issue is that this also changes the way of communication, which will be using online communication. Previously, employees had to go to the office and have face-to-face interaction with other employees. Still, now, all communication is done online, so it may affect employees working from home. Therefore, this research intends to examine the effectiveness of online communication on job performance among working-fromhome employees. The present study deployed a quantitative research method involving questionnaires as a research instrument to 202 employees working from home. A convenient random sampling technique were used to acquire the number of respondents. Results show that Microsoft Teams is the most adequate online communication tool used by respondents of the study. The study found that respondents agree that working from home will improve their work performance. In order to have more effective communication in an organization, management plays an important role in the communication process between employees and employers. Standardized communication practices such as regular or weekly meetings can be conducted for the whole team to enhance relationship bonds between employees.